ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MEMBELI PRODUK SECARA ONLINE (STUDI MAHASISWA UNIVERSITAS NEGERI ISLAM SULTAN THAHA KOTA JAMBI) - Sintia Angela Sari; Rofiqoh Ferawati; Achyat Budianto (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2025)
This study aims to analyze the factors influencing students’ purchasing decisions at Universitas Islam Negeri Sultan Thaha Jambi in buying products online. The independent variables in this research are price, product quality, trust, convenience, and promotion, while the dependent variable is the purchase decision. The research method applied is a quantitative approach with an associative type. Data were collected through questionnaires distributed to 100 student respondents who had purchased products online. The data were analyzed using multiple linear regression with SPSS. The results indicate that simultaneously, price, product quality, trust, convenience, and promotion significantly affect purchasing decisions. Partially, price, product quality, and trust have a significant effect, while convenience and promotion show no significant effect. The most dominant factor influencing students’ online purchasing decisions is price. These findings imply that online businesses should prioritize pricing strategies and product quality improvement to attract and retain customers.